Comparison of Quarter Life Crisis in Adolescents - Fikri, Aizatul; Syaifulloh, M. Rosyid; Assauri, M. Dery Siraj; Santoso, Revaliya Maghfirani; Desandyansyah, Salmania Khnsa' Nabila; Gunawan, Yuvica Novita (Inovasi Lokal, 2024)
Quarter Life Crisis is a new term related to the stages of human socio-emotional development. Approaching the age of 25, individuals usually have to face new life situations such as work and marital status, as well as changes in mindset that are more mature from adolescence to adulthood. This situation also makes individuals at the peak of self-maturity, when entering the age of 25, question their own lives, doubt their own choices, feel confused about the things they are living, and begin to recall the past. The type of research used for this research is qualitative with interview techniques. The primary data source is in the form of interviews regarding their understanding of the quarter life crisis. Our secondary data sources are information from journals or other internet sources. Interview results show that individuals in early adulthood who experience a quarter life crisis feel anxious and afraid, which is caused by uncertainty about the future, social pressure, hormonal changes, and others. In the publication, we present two contents on the Instagram page (reels and feed).Our reels upload reached 714 views until October 16, 2023 at 4.10 PM. Meanwhile on Instagram feeds, our content reached 36 users within 15 hours through mass media the information conveyed can be accessed more widely and spread quickly. It is expected that this social campaign can change several aspects of the target audience, such as awareness, attitude, & action.